Prevalence of Helicobacter pylori among patients with different gastrointestinal disorders in Saudi Arabia (Faculty of Medicine Universitas Indonesia, 2016)
Background: Helicobacter pylori is an important gastrointestinal pathogen associated with gastritis, peptic ulcers, and an increased risk of gastric carcinoma. The present study was carried out to determine the relationship between this organism with different gastrointestinal ailments. Methods: 150 outpatients referrals to Saudi Arabian Medical City, Riyadh, Kingdom of Saudi Arabia was recruited in January to June 2015. Each patient was subjected to endoscopic examination. Biopsy specimens were taken from the stomach for rapid urease test and culture. Suspected H. pylori colonies were subjected to colony morphology identification, microscopical examination and biochemical reactions. The samples were also subjected to PCR to detect ureA subunit of urease gene. Results: The endoscopic examination of patients revealed normal, gastric ulcer, duodenal ulcer, gastritis, and gastric cancer with a rate of 20.7%, 20%, 24%, 33.3%, and 2%, respectively. Direct smear exam revealed that 52% of patients were H. pylori positive while culture and rapid urease test showed a prevalence of 71.33%. Fifty four biopsies (36%) were urease positive after 1 hour at room temperature, 39 (62%) after 1 hour incubation at 37°C and 14 (71.33%) after 24 hours incubation. Isolated H. pylori showed that they were catalase, oxidase, and urease positive. PCR results showed 411-bp fragment, which is indicative for the ureA subunit of urease gene. Conclusion: The prevalence of H. pylori infection was high among tested population. Strong association between H. pylori and duodenal ulcer was noticed. A 411-bp fragment indicative of the ureA subunit of urease gene was detected in all the tested isolates.